Essential Attributes of Clear Aligner Therapy in terms of Appliance Configuration, Hygiene, and Pain Levels during the Pandemic: A Brief Review - Anand Marya; Adith Venugopal; Nikhilesh Vaid; Mohammad Khursheed Alam; Mohmed Isaqali Karobari (Pain Research and Management)
Fixed orthodontic treatment has been compromised at many levels during the pandemic period, as clinics underwent a prolonged lockdown and patients could not be treated regularly. With the end of the pandemic nowhere in sight, may be it is time to put newer tools, such as clear aligner therapy, for better use. Fixed orthodontic appliances by nature are not always self-limiting, which, if left unmonitored over a long period may cause undesirable side effects, pain, and discomfort. The undesired tooth movements that may occur with arch wire-guided mechanics in addition to problems with cut wires or removed brackets may be minimized with the use of aligners. While the benefits of using aligners are for all to see, they do require extensive planning and careful evaluation of the progress. This article reviews the advantages of using aligners during the pandemic period and how it can be beneficial in helping orthodontists resume their practice.